(untitled) (Avocetta, 2017)
This research aims to fill a knowledge gap on the current status and distribution of the Golden Eagle’s Aquila chrysaetos nesting pairs in Sardinia. To date, no recent data or censuses in the scientific bibliography about the situation of this raptor in Sardinia exist (Fasce & Fasce 1992, Asuni et al. 2003, 2004-2005, Brichetti & Fracasso 2003, Grussu 1995-1996). The only scientific reference is that by Helmar Schenk, dating back to 1976, who estimated the Sardinian population of Golden Eagle at a minimum of 25 pairs and a maximum of 38 (Schenk 1976). This species was considered to be at risk, mainly because of direct threats by farmers due to the supposed damage caused to their livestock (Fasce & Fasce 1984). More recently, several authors documented a much higher number of pairs, estimating 40/50 pairs of Golden Eagles breeding in Sardinia (Schenk 1995, Asuni et al. 2003, Fasce & Fasce 2003). These estimates are mostly based on generic assumptions, without precise territorial references, with the exception of some investigations, carried out with rigor and over a period of several years but concerning only limited portions of the island territory. The most recent report related to a specific geographic area is dated 2009 and covers the territory of the former Province of Olbia Tempio, where 7 nesting pairs were censused and 8-10 probable pairs were estimated (Trainito 2009). The data provided in this report covers about 80% of the island’s territory, corresponding to perfectly identified geographic areas, and are the result of direct field research about the observation of pairs during the courtship period, the verification of the occupied nests, the successful outcome of chick rearing, the analysis of the behavior of young immediately after their fledging, as well as the estimation of the occasional groupings of more “families” in the autumn period. Unpublished data originate from direct observations and from verified testimonies.